pH Dependence of the Km(CO(2)) of Ribulose 1,5-Diphosphate Carboxylase - Bowes, George (1975)
The Km(CO(2)) values of ribulose 1,5-diphosphate carboxylase in freshly ruptured spinach (Spinacia oleracea L.) chloroplasts and in the purified form isolated from spinach leaves were found to be pH dependent. Raising the pH of the assay solution produced a substantial decrease in the Km(CO(2)) of both enzyme systems. In freshly ruptured chloroplasts at pH 7.2 the Km(CO(2)) was 25 μm, at pH 8 it decreased to 19 μm, and at pH 8.8 a further decrease to 7 μm was found. With the purified enzyme at pH 7.2 the Km(CO(2)) was 147 μm, while the corresponding Km values for pH 8 and 8.8 were 34 and 15 μm CO(2), respectively. The latter figure approximates the physiological Km(CO(2)) of 10 μm estimated for photosynthesizing leaves and intact chloroplasts. The maximum velocity for both enzyme systems at optimum substrate levels was at pH 8, but the highest calculated rate of CO(2) uptake at atmospheric CO(2) levels occurred at pH 8.8. These results support the proposal that the light-induced efflux of protons out of the chloroplast stroma may be a major factor involved with the reported in vivo light activation of ribulose 1,5-diphosphate carboxylase.